Pengembangan Media Pembelajaran Augmented Reality Card pada Materi Virus untuk Meningkatkan Hasil Belajar Kognitif Siswa - Aprianingsih Umar; Ilyas H. Husain; Nurul Fajryani Usman; Frida Maryati Yusuf; Syam S. Kumaji (UNIB Press, 2026)
This research aims to develop Augmented Reality Card-based learning media on virus material and to determine the level of validity, practicality, and cognitive learning outcomes of students through a limited scale trial. This study uses the Research and Development (R&D) method with the ADDIE development model. The research subjects consisted of 34 grade X students at SMA Negeri 1 Tibawa. The instruments used included a questionnaire validation sheet from media experts and material experts, a questionnaire response from teachers and students, and a learning outcome test in the form of a pretest and posttest. The results showed that the AR Card media obtained an average validation percentage of media experts of 95% and material experts of 93% with very feasible criteria. Teacher responses obtained a percentage of 95% and student responses of 81% with a very practical category. In addition, the results of the N-Gain analysis in a limited scale trial of 0.67 showed that the use of AR Card media was able to improve students' cognitive learning outcomes in the moderate category. Thus, AR Card-based learning media was declared valid, practical, and used in biology learning on virus material.